Transformational Leadership in Supporting Innovative Digital Governance - DEMA, HERMAN; HAMID, HARIYANTI; BARISAN, BARISAN (Jurnal Studi Pemerintahan, 2023)
This research is motivated by various failures of several government leaderships in running digital government and resulting in low innovation. This study aims to analyze transformational leadership in supporting innovative digital governance. Digital governance emphasizes the aspect of using data and platforms for the public to be able to access government information and services anytime and anywhere by utilizing online network devices. The government of innovation emphasizes the creation of new things that are sup- ported by human intelligence. Data were taken through interviews and through online media and then analyzed using NVivo 12 Plus. The results show that transformational leadership provides good support for digital governance. Digital governance can contribute to transformational leadership in creating innovations. E-governance has a positive impact on the efficiency and effectiveness of public governance in relation to human relations with humans, human relations with government, and government relations with other institutions.